Final irrigation protocols in endodontics: A narrative review (Research, Society and Development, 2025)
This study is a narrative literature review aimed at analyzing the various final irrigation protocols currently used in endodontics, highlighting their characteristics, advantages, and limitations. It is a qualitative, retrospective, and descriptive review based on searches conducted in the PubMed, LILACS, and SciELO databases, including publications in Portuguese and English. Seven irrigation techniques were identified and compared: Conventional Irrigation (CI), Manual Dynamic Activation (MDA), Passive Ultrasonic Irrigation (PUI), Continuous Ultrasonic Irrigation (CUI), EasyClean Activation (ECA), XP Endo Finisher, and Sonic Irrigation. CI showed limitations in smear layer removal and complete canal disinfection. Although effective, MDA may lead to debris compaction. Ultrasonic techniques demonstrated high efficacy in debris removal but may pose a risk of tissue damage. Sonic irrigation and EasyClean activation emerged as promising alternatives, with effective biofilm removal and lower risk to periapical tissues. The study concludes that ECA and XP Endo Finisher are promising techniques. Technique selection should be case-specific. Periodic reviews and clinical studies are essential to keep up with advancements and ensure optimal patient care. Collaboration among researchers, clinicians, and manufacturers is crucial for the continuous development of endodontics.